Evolution of Thin Film Morphology Modeling and Simulations - Pelliccione, Matthew; Lu, Toh-Ming (Springer Series in Materials Science,, 2008)
Thin film deposition is the most ubiquitous and critical of the processes used to manufacture high tech devices. Morphology and microstructure of thin films directly controls their optical, magnetic, and electrical properties. This book focuses on modeling and simulations used in research on the morphological evolution during film growth. The authors emphasize the detailed mathematical formulation of the problem both through numerical calculations based on Langevin continuum equations, and through Monte Carlo simulations based on discrete surface growth models when an analytical formulism is not convenient. Evolution of Thin-Film Morphology will be of benefit to university researchers and industrial scientists working in the areas of semiconductor processing, optical coating, plasma etching, patterning, micro-machining, polishing, tribology, and any discipline that requires an understanding of thin film growth processes. In particular, the reader will be introduced to the mathematical tools that are available to describe such a complex problem, and appreciate the utility of the various modeling methods through numerous example discussions. For beginners in the field, the text is written assuming a minimal background in mathematics and computer programming. The book will enable readers themselves to set up a computational program to investigate specific topics of interest in thin film deposition.